Virtual Tour Implementation Scenario As Sustainable Tourism To Restore Tourism Sector In Banyuwangi - Retnosari, Dyah Silvian; Nuraini, Mia Wahyu (JURNAL DESTINASI PARIWISATA; Vol 12 No 1 (2024): VOL 12, NO 1 (2024): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2024.v12.i01.p17, 2024)
This research discusses the design of scenarios for the implementation of virtual tours for Sustainable Tourism as an effort to recover the tourism sector in Banyuwangi. Virtual tours are one of the new innovation alternatives that can be used in promoting and developing tourism in Banyuwangi. Virtual tour is planned to be a digital platform where service providers can participate in developing tourism business to revive the economy in the tourism sector in Banyuwangi. This virtual tour is applied by charging a fee in its use in exchange for the entrance fee to the tourist destinations visited. The study used a qualitative descriptive approach with data collection derived from secondary data and primary data. This research method is carried out inductively by conducting an analysis based on the data obtained and developed according to the topic studied. The results of this study show that virtual tours can help the development of the tourism sector and Sustainable Tourism in Banyuwangi through the application of technology and digital media. The scenario planning in this study is quite promising, as evidenced by the results of a comparative analysis of its application with tourism in general and the calculation of NPV that has been calculated. Keywords: Development program, Sustainable Tourism, Vitual tour